IoT-based home automation system using Arduino UNO / Mohammad Ammar Aiman Hashim ... [et al.] - Hashim, Mohammad Ammar Aiman; Mohd Fauzi, Mohamad Aiman; Mohd Zin, Mazratul Firdaus; Ku Mohd Noh, Ku Siti Syahidah (UiTM Cawangan Negeri Sembilan, 2023)
This project shows the design and prototype of a better home automation system that uses WiFi technology to connect all of its parts. The proposed system has two main parts. The first is the software, which is the Internet of Things (IoT), which is the web server through the Blynk application. This is the part of the system that monitors users' home appliances. Users and system administrators can monitor the system from close by (via LAN) or far away (via the internet). The second part is the hardware interface module, which uses an Arduino UNO to connect to sensors in the right way and is the home automation system's actuator. The system is user-friendly since it can be managed and operated easily. The system has successfully operated as expected with the implementation of multiple sensors to actuate the system's operation. The proposed system has the potential to be commercialized due to its simplicity when applied to home automation systems.